Acute lead poisoning: a diagnostic challenge in the emergency department. Issue 1 (20th January 2021) - Gopinath, Bharath; Kappagantu, Vignan; Mathew, Roshan; Jamshed, Nayer
Abstract : Acute abdominal pain is a common presentation to the emergency department (ED). Ruling out life-threatening causes and giving pain relief are the most important tasks in ED. We describe a 32-year-old man who presented to ED with abdominal pain and vomiting which was unrelieved by usual doses of analgesic. Extensive investigations revealed no significant abnormalities. On further probing, he admitted taking traditional medications for infertility. The toxicological panel revealed a high blood lead level, leading to a diagnosis of acute lead toxicity. Chelation therapy with D-penicillamine was initiated and the patient's abdominal pain resolved within 4 days.